2016
DOI: 10.1016/j.jbtep.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sustained smoking abstinence is associated with reductions in smoking-specific experiential avoidance among treatment-seeking smokers

Abstract: Background and Objectives Smoking-specific experiential avoidance is related to the maintenance of cigarette smoking. However, it is unclear whether sustained smoking abstinence is associated with subsequent reductions in smoking-specific experiential avoidance. Methods Daily smokers (n = 149) underwent a cessation attempt in the context of a 4-session smoking cessation treatment trial. Participants provided biochemical verification of smoking status at 1 week, 2 weeks, and 1 Month post-quit day. Smoking-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Previous studies have found that ACT-based treatment resulted in greater decreases in smoking-specific experiential avoidance (AIS) that mediated the effects of the treatment on smoking outcome (Bricker et al, 2013; Gifford et al, 2004, 2011). Other research has shown that smoking abstinence elicits reductions in smoking-specific experiential avoidance (Farris et al, 2016). In the current study, participants in the ST condition had significantly greater increases in a measure of rumination and avoidance (BADS-AR) compared to those in the DT treatment, but no differences in changes in AIS or other process measures were observed across treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that ACT-based treatment resulted in greater decreases in smoking-specific experiential avoidance (AIS) that mediated the effects of the treatment on smoking outcome (Bricker et al, 2013; Gifford et al, 2004, 2011). Other research has shown that smoking abstinence elicits reductions in smoking-specific experiential avoidance (Farris et al, 2016). In the current study, participants in the ST condition had significantly greater increases in a measure of rumination and avoidance (BADS-AR) compared to those in the DT treatment, but no differences in changes in AIS or other process measures were observed across treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, experiential avoidance has been implicated in the aetiology and maintenance of diverse forms of psychopathology, including anxiety‐related disorders , post‐traumatic stress disorder , depression , and substance‐related disorders . Experiential avoidance has also been linked to several health problems; it has, for example, been implicated in the maintenance of cigarette smoking ; it has been found to mediate the relationship between bowel disease symptomatology and QoL , and to function as a moderator between breast cancer anxiety and mammography use .…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Furthermore, the experiential avoidance specific to smoking is linked with more significant negative effects, desires, and nicotine withdrawal when beginning the therapy for quitting smoking. 35 Moreover, in experiences of internal disturbances (negative affect and withdrawal symptoms) while trying to quit, smokers that are highly avoid due to experience are more probable to have reducing their smoking rates, even after the therapy for quitting smoking, compared to smokers having fewer amounts of EA. 36 Results showed that EA was negatively associated with internal discomfortness on smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there was no contrast between the two groups after the therapy, the results showed that the participants in the ACT group reached better results in smoking rates out of doing it in an abiding manner after one year. 7 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%